Pelaksanaan Asas Dominus Litis Jaksa pada Tahapan Penuntutan Rehabilitasi Pelaku Penyalahgunaan Narkotika Berdasarkan Asesmen Terpadu - Rusdiana, Shelvi; Jaya, Febri; Anggresca, Risella Vini (University of Merdeka Malang, 2024)
Narcotics are substances or drugs derived from plants or non-plants that can cause a decrease or alteration in consciousness, loss of sensation, reduction or elimination of pain, and can lead to dependence. In fact, Law Number 35 of 2009 concerning Narcotics classifies between traffickers and users, each with different penalties, namely rehabilitation demands based on the stages of the case by the Prosecutor's Office following the principle of dominus litis, where the prosecutor controls the case. This study aims to examine the qualifications of criminal narcotics regulations with rehabilitation demands and to understand and analyze the implementation of the principle of dominus litis by prosecutors in handling criminal narcotics cases based on integrated assessments. This research employs a normative juridical research method that starts from statutory regulations, books, scientific journals with a legislative approach consisting of Law Number 35 of 2009, PERJA 029 of 2015 regarding Technical Instructions for Handling Narcotics Addicts and Victims of Narcotics Abuse into Rehabilitation Institutions, Guideline Number 18 of 2021 regarding the Settlement of Criminal Cases of Narcotics Abuse through Rehabilitation with a Restorative Justice Approach as the Implementation of the Dominus Litis Principle, using a conceptual approach. The demand for rehabilitation becomes the primary goal of case resolution in line with the principle of utility based on specific classifications according to prevailing provisions.